Persistency and milk secretion coefficients of the indigenous and crossbred cattle at Asela, Ethiopia - Kiwuwa, G.H.; Getachew Worku; Mukasa-Mugerwa, E. (1985)
Examines milk production during early, middle and late phases of lactation in indigenous (Bos indicus) Arsi and Zebu cattle and their crosses with Jersey and Friesians. Analyses milk yield, lactation persistency and milk secretion coefficients.